Participants' Narratives of the Fulbright FLTA Program on their Intercultural and Professional Experience - Angela Patricia Velásquez-Hoyos; Lizeth Andrea Martínez-Burgos (Asociación Colombiana de Profesores de Ingles, 2023)
This paper reports the results of a narrative inquiry study on exchange programs, intercultural awareness, and professional development in eight former participants of the Fulbright Foreign Language Teaching Assistant -FLTA- program. This study used written narratives to collect data from eight participants of the FLTA scholarship program who belonged to the cohort 2017-2018. The results of this study showed that after being a FLTA, participants improved their English language skills; they became more aware of their teaching practices by implementing and adapting different teaching methodologies, they experienced cross-cultural interaction, and understood better cultural differences which really fostered their personal and professional development as English language teachers in their home countries.